Pocket Book for Early Literacy Skills Based on 4P Media - Rohita; Martini Jamaris; Sri Wulan (Universitas Pendidikan Ganesha, 2024)
Many early childhood education programs still heavily rely on worksheets, thereby limiting children's opportunities to engage in play-based literacy activities that support their natural development. Moreover, teachers often lack practical and easy-to-use learning resources to stimulate early literacy skills in accordance with children's developmental stages. This study aims to develop a pocket book that can be used by teachers to enhance their understanding of early literacy skills in children and ways to stimulate them. The research method used is development research with the ADDIE model, limited to the implementation stage. The sample at the implementation stage consisted of 6 kindergarten teachers and 14 students from the Early Childhood Teacher Education program. Data collection was carried out through observation, validation, and questionnaires. Data were analyzed using descriptive statistical techniques based on validation results from three experts, practitioners, as well as responses from kindergarten teachers and students. The results in the development phase showed that the pocket book was rated as